(untitled) (Research, Society and Development, 2021)
This report aims to share the experience lived in the Education through Work for Health Program (PET-Saúde) Interprofessionality in a Family Health Strategy (FHS) team from the city of Governador Valadares (GV), Minas Gerais, with focus on the care of health professionals working in this FHS. Situational diagnosis and Situational Strategic Planning (PES) were carried out, covering respectively: survey and prioritization of problems; explanatory, normative, strategic and tactical-operational moment, in order to achieve the objective image of “Improving care for ESF professionals”. The interventions carried out were: workshops and integrative dynamics with health professionals; construction and distribution of the booklet on worker health care; elaboration of a letter to the health managers of the city. As a result of these activities, the following stand out: the effective dissemination of information about the service network to workers in this municipality. This helped the workers to become active in this process, and for the creation of bonds between health workers, providing an improvement in the care with the service users.